2023
DOI: 10.3390/s23218936
|View full text |Cite
|
Sign up to set email alerts
|

Graph Neural Networks for Parkinson’s Disease Monitoring and Alerting

Nikolaos Zafeiropoulos,
Pavlos Bitilis,
George E. Tsekouras
et al.

Abstract: Graph neural networks (GNNs) have been increasingly employed in the field of Parkinson’s disease (PD) research. The use of GNNs provides a promising approach to address the complex relationship between various clinical and non-clinical factors that contribute to the progression of PD. This review paper aims to provide a comprehensive overview of the state-of-the-art research that is using GNNs for PD. It presents PD and the motivation behind using GNNs in this field. Background knowledge on the topic is also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…The primary objective is to elevate the assessment of PD patients by establishing a robust foundation for personalized health insights through the development of Personal Health Knowledge Graphs (PHKGs) [1][2][3]. Additionally, a personal health Graph Neural Network (PHGNN) is developed leveraging the PHKG to formalize the representation of related sensors and PHR integrated/unified data at a higher level of abstraction [4]. This paper, as an extension of our previous related work [5], provides a detailed exploration of the Wear4PDmove ontology and evaluates its integration within the development of an experimental PHKG [5].…”
Section: Introductionmentioning
confidence: 99%
“…The primary objective is to elevate the assessment of PD patients by establishing a robust foundation for personalized health insights through the development of Personal Health Knowledge Graphs (PHKGs) [1][2][3]. Additionally, a personal health Graph Neural Network (PHGNN) is developed leveraging the PHKG to formalize the representation of related sensors and PHR integrated/unified data at a higher level of abstraction [4]. This paper, as an extension of our previous related work [5], provides a detailed exploration of the Wear4PDmove ontology and evaluates its integration within the development of an experimental PHKG [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, findings show that men are more prone to the disease compared to women ( 6 ). It is characterized by a range of symptoms including tremors, rigidity, and dyskinesia ( 8 ). However, available experiments have confirmed that the effects of PD on patients are no longer limited to these aspects; it also diminishes the sense of smell and leads to depression, immune dysfunction, and even hallucinations ( 6 , 9 ).…”
Section: Introductionmentioning
confidence: 99%